2003
DOI: 10.1159/000071338
|View full text |Cite
|
Sign up to set email alerts
|

Modern Phase-Specific Management of Acute Pancreatitis

Abstract: The management of acute necrotizing pancreatitis has changed significantly over the past years. In contrast to the early surgical intervention of the past, there is now a strong tendency towards a more conservative approach. Initially, severe acute pancreatitis is characterized by the systemic inflammatory response syndrome. Early management is non-surgically and solely supportive. A specific treatment still does not exist. In cases of necrotizing disease, prophylactic antibiotics should be applied to reduce l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 98 publications
1
24
0
2
Order By: Relevance
“…Six surviving patients (8%) required surgical necrosectomy because percutaneous therapy failed in controlling sepsis. The mortality rate in this study was 34% which is within the expected range of 20%-40% [10][11][12] reported in the literature. Considering that the study population represented a seriously ill subset of patients as evidenced by high clinical and radiological scores, a mortality rate of 34% is an acceptable outcome.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Six surviving patients (8%) required surgical necrosectomy because percutaneous therapy failed in controlling sepsis. The mortality rate in this study was 34% which is within the expected range of 20%-40% [10][11][12] reported in the literature. Considering that the study population represented a seriously ill subset of patients as evidenced by high clinical and radiological scores, a mortality rate of 34% is an acceptable outcome.…”
Section: Discussionsupporting
confidence: 82%
“…The standard treatment has traditionally been surgery [5,6] . By using modern surgical techniques like open packing, repeated laparatomies, closed packing or closed continuous lavage mortality rates could be decreased to 20%-40% [7][8][9][10][11][12] . However, these techniques are associated with a considerable surgical trauma which often causes escalation of multiorgan failure and sepsis [7,13] .…”
mentioning
confidence: 99%
“…Autopsy results confirm that pulmonary complications were among the most common causes of death during the first week of disease progression [31] . Hypoxia is associated with multiple organ failure and high mortality [32][33][34] .…”
Section: Arterial Blood Gas (Abg)mentioning
confidence: 62%
“…In the management of documented pancreatic infection surgical removal of necrotic tissue is of paramount importance and generally accepted, since conservative treatment alone was associated in some studies with an unacceptably high mortality of up to 100% [4,75] . The occurrence of infection must be suspected whenever the clinical situation in a patient with necrotic pancreatitis is deteriorating with increasing signs of infl ammation (fever, CRP 1 180 mg/ml, leukocytosis), increasing pain, hemodynamic instability and progressive multi-organ dysfunction syndrome.…”
Section: Indications For Surgery and Timing Of The Interventionmentioning
confidence: 99%